PRELIMINARY STUDIES OF THE EFFECT OF IRRADIATION ON SEEDLING PERFORMANCE OF COWPEA (VIGNA UNGULCULATA (L.) WALP). - OBISESAN, I. O.; AMUJOYEGBE, B. J. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
A study was conducted to assess the effect of six doses of gamma-ray irradiation, viz, 0, 10, 15, 20, 25 and 30 krads on the seedling performances of Cornetto and OB89/4 varieties of cowpea which are of Italian and Nigerian origin respectively. The effect of irradiation was observed on germination percentage (G%), days to 50% germination (DTG50%). leaf area at 2 weeks (LA2wk), percentage seedling with trifoliate leaves (%STL) and seedling height (SH). There were significant variety X dose interaction for G%, LA2wk and %STL. The overall range of G% and %STL was smaller for Cornetto which had a longer period to attain 50% germination. OB89/4 performed better at low dosages (0-15 krads) but Cornetto is more resistant to irradiation at higher dosage (20-30 krads). Using a regression model it was established that Cornetto and OB89/4 required differential irradiation treatment in order to achieve the same effect on seedling traits.